Podcast-based instruction with Banggai culture: Enhancing EFL students’ communicative grammar - Sukma Widya Sasmi Sabbu; Srilidiawati Epa (English Learning Innovation, 2026)
Grammar instruction in EFL contexts has often been criticized for being overly structural and disconnected from authentic communication, leaving students with difficulties in applying grammar during speaking. To address this issue, this study aimed to enhance EFL students’ communicative grammar competence through podcast-based instruction integrated with Banggai cultural narratives. The research employed an Educational Design Research (EDR) framework using a mixed-method sequential explanatory design, conducted with second-semester students of the English Language and Culture Study Program at Universitas Tompotika Luwuk. Data were collected from 41 students through test, questionnaires, interviews, and observation, then analyzed using descriptive statistics (SPSS 25) and thematic coding (NVivo 10). The findings revealed significant improvement in students’ grammar performance, with mean scores rising from 54.41 in the pre-test to 80.24 in the post-test. The questionnaire results further indicated that the majority of students strongly agreed or agreed that podcasts made grammar learning clearer, increased their confidence in speaking, and fostered a greater appreciation of Banggai culture. Thematic analysis of interviews confirmed these perceptions, highlighting motivation, engagement, and cultural relevance as key factors in learning success. This study concludes that integrating local culture into podcast-based instruction offers both pedagogical and cultural benefits, making grammar learning more meaningful, communicative, and contextually grounded. The model not only improves linguistic competence but also promotes cultural awareness, offering a sustainable and innovative direction for EFL grammar instruction in culturally diverse contexts.